Expression of Estrogen Receptor and Progesterone Receptor Status In Patients of Carcinoma of Ovary and Carcinoma of Endometrium - Irshad, Razia; Haider, Ghulam; Hassan, Anusha; Hashmi, Madiha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the expression of estrogen and progesterone receptor status in patients of carcinoma of ovary and carcinoma of endometrium.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medical Oncology of Jinnah Postgraduate Medical Centre, Karachi Pakistan, from Feb 2019 to Feb 2020.Methodology: Seventy females of age 18-70 years with histologically proven diagnosis of ovarian carcinoma or endometrial carcinoma were included in the study. Each patient was interviewed for obtaining demographic details, medical history and presenting symptoms with help of validated questionnaire. Immunohistochemical analysis was performed for confirming estrogen and progesterone receptor expressions.Results: Out of 72 evaluated patients, ovarian carcinoma was present in 45(62.5%) patients and endometrial carcinoma in 27(37.5%) patients having mean age of 52.6±10.1 (30-69) years. Mean body mass index was 30.4 ± 5.7(18-39) Kg/m2 with obesity in 42(58.3%) patients. Immunohistochemistry showed estrogen receptor positive in 32(71.1%) and 18(66.7%) patients, estrogen receptor negative in 13(28.9%) and 9(33.3%) patients, progesterone receptor positive in 31(68.9%) and 19(70.4%) and progesterone receptor negative in 14(31.1%) and 8(29.6%) patients of ovarian and endometrial carcinoma respectively. Overall it showed higher expression of ER and PR in patients of ovarian and endometrial carcinoma.Conclusion: The study concludes that approximately two third of patients showed estrogen and progesterone receptor expression in ovarian and endometrial carcinoma. These ER and PR expressions have capability to be utilized as prognostic indicator for ovarian and endometrial carcinoma.